ANALISIS PROGRAM KESELAMATAN DAN KESEHATAN KERJA DI BAGIAN PRODUKSI DENGAN MENGGUNAKAN METODE 5S (Sudi Kasus PT Pionirbeton Industri Plant Yogyakarta) - Hendri Yanto (Spektrum Industri, 2020)
PT. Pionir Beton Industri Plant Yogyakarta has not implemented the occupational health and safety program optimally. The number of work accidents occurred on PT. Pionir Beton Industri Plant Yogyakarta from 2015 to 2017 were 10, 8, and 7 events. The working condition indicated that the stuffs or the rest of production scattered on the production floor, the company has not implemented the material arrangement yet, not all workers maintain the cleanliness, undisciplined workers. The analyze of problem was conducted using 5S method, and also measure the frequency rate, severity rate, incidence rate, and frequency severity indicator. The frequency rate results showed 75.483 hours, 60.386 hours, and 52.838 hours from 2015 to 2017. The Severity rate results showed 679.347 days, 603,864 days and 366.123 days from 2015 to 2017. The Incidence Rate results showed 21,7%, 17,4%, and 15,2% from 2015 to 2017. The Frequency Severity Indicator results showed 51.279 times, 36.386 times, and 29.912 times from 2015 to 2017. The work productivity was strongly influenced total work hours of workers and the number of workdays lost. The 5S method analyze results showed that the actual condition didÂ not meet the requirement ofÂ 5S method.